Integral adhesive-free hierarchical porous MWW molecular sieve as well as preparation method and application thereof
Through the multi-stage pore MWW molecular sieve without binders, the problem of blockage of active site utilization and complex process caused by binders in the existing isopropyl benzene synthesis process is solved, and the direct conversion and efficient catalysis of isopropyl benzene is achieved, which simplifies the The process flow and improve reaction efficiency and product quality.
Patent Information
- Application Number
- CN202310869143.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
In the existing isopropyl benzene synthesis process, the use of fine powder zeolite catalysts requires a binder, which leads to the hindering of the utilization of active sites, affecting the diffusion and reaction selectivity of reactant molecules. The process is complicated, and two reactors need to separate the isopropyl benzene. Benzene, which increases equipment investment and impurity generation.
Using a multi-stage pore MWW molecular sieve without binder, it has microporous and mesoporous structures, and the mesoporous accounts for more than 65% of the total pore volume. An integral catalyst with regular mesoporous and microporous structures is prepared by a specific preparation method. , used for the alkylation reaction of isopropyl benzene, simplifying the process flow and improving catalytic activity and selectivity.
The direct conversion of isopropyl benzene is achieved, the process flow is shortened, equipment investment is reduced, reaction efficiency and product quality is improved, by-product generation is reduced, and the process flow is simplified.
Smart Images

Figure CN119306234A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an MWW molecular sieve, and in particular to an MWW molecular sieve and a preparation method and application thereof. Background Art
[0002] Isopropylbenzene is an important organic chemical raw material for producing phenol and acetone. The synthesis of isopropylbenzene mainly adopts the method of alkylation of benzene and propylene. UOP and Mobil processes are two representative processes for producing isopropylbenzene. The former uses β-type molecular sieves, and the latter uses MWW type molecular sieves as catalysts. After a period of reaction, the UOP process needs to increase the temperature to regenerate the catalyst by hot benzene washing, while the Mobil process does not require regeneration. Therefore, the promotion of the UOP process has been subject to certain restrictions in recent years.
[0003] The synthesized zeolite catalyst is usually a fine powder with a particle size of several nanometers to several microns. Such fine powder must be formed into different forms such as granules and strips together with inorganic binders (clay, alumina, etc.) to meet the application requirements. The presence of binders disperses and dilutes the active components, blocks the pores of the zeolite molecular sieve, hinders the utilization of active sites, affects the diffusion of reactant molecules, and objectively reduces the selectivity of the reaction. Combining zeolite powders into a monolithic catalyst without a binder is an interesting research hotspot. Monolithic catalysts refer to integrated catalysts with many narrow, neatly arranged pores. Compared with traditional molded granular catalysts, monolithic catalysts can improve the efficiency of catalysis, improve the selectivity of the reaction, and help to achieve low energy consumption, low emissions and safe process. If the monolithic binder-free molecular sieve catalyst can be applied to the alkylation reaction of isopropylbenzene preparation, it will play a good role in promoting the optimization of the entire process.
[0004] In the prior art, benzene and propylene are first subjected to an alkylation reaction in an alkylation reactor. After the polysubstituted isopropylbenzene generated by the alkylation reaction is separated by a distillation system, the polysubstituted isopropylbenzene is mixed with benzene and then enters a single-bed transalkylation reactor for transalkylation reaction. In the transalkylation reaction of benzene and polyisopropylbenzene, the transalkylation reaction of polyisopropylbenzene often produces more impurity n-propylbenzene, which seriously reduces the quality of the product isopropylbenzene. In patent documents such as CN102464563A, CN102464564A, and CN102464565A, the conversion rate of polyisopropylbenzene is improved, the n-propylbenzene generated by transalkylation is reduced, the generation efficiency is improved, and the product quality is improved, but it needs to use two reactors. Therefore, it is of great significance to continue to seek a simpler process and reactor for industrial production. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, the present invention provides a multi-stage pore MWW molecular sieve, which, when used as a cumene synthesis catalyst, can directly convert diisopropylbenzene, so that the reactor is simplified from two to one, shortening the process flow and reducing equipment investment.
[0006] In the first aspect, the present invention provides an integral binder-free multi-level pore MWW molecular sieve, wherein the molecular sieve has micropores and mesopores, the micropores are pores with a pore diameter less than 2nm, the mesopores are pores with a pore diameter of 2 to 50nm, and the mesopores account for more than 65% of the total pore volume.
[0007] In some embodiments, the mesopore includes a first mesopore, a second mesopore and a third mesopore, the pore size d1 of the first mesopore satisfies: 2.0nm<d1≤5.0nm, the pore size d2 of the second mesopore satisfies: 5.0nm<d2≤20nm, and the pore size d3 of the third mesopore satisfies: 20nm<d3<50nm.
[0008] In some embodiments, the molecular sieve has one or more of the following features (a) to (h):
[0009] (a) The acid amount of the molecular sieve is 1 to 2 mmol / g, preferably 1 to 1.5 mmol / g;
[0010] (b) The specific surface area of the molecular sieve is 450 to 600 m 2 / g, preferably 450 to 550 m 2 / g;
[0011] (c) the average pore size of the molecular sieve is 3 to 5 nm, preferably 3.2 to 4.5 nm;
[0012] (d) The total pore volume of the molecular sieve is 0.25 to 0.75 cm 3 / g, preferably 0.30 to 0.70 cm 3 / g;
[0013] (e) The micropore volume of the molecular sieve is 0.25 to 0.45 cm 3 / g, preferably 0.28 to 0.42 cm 3 / g;
[0014] (f) the pore volume of the first mesopores accounts for 25% to 40% of the total pore volume, the pore volume of the second mesopores accounts for 25% to 40% of the total pore volume, and the pore volume of the third mesopores accounts for less than 15% of the total pore volume, preferably 7-12%;
[0015] (g) The molecular sieve has a closed hysteresis loop at P / P0=0.4-0.99 on the nitrogen adsorption-desorption curve, and the absorption mass difference between the adsorption curve and the desorption curve is 0-4cm 2 / g; preferably, the starting position of the closed hysteresis loop is at P / P0=0.45-0.99, and the absorption mass difference between the adsorption curve and the desorption curve is 0-3.5cm 2 / g;
[0016] (h) The molecular sieve X-ray diffraction (XRD) spectrum has characteristic peaks at 2θ angles of 7.5°±1°, 9.5°±1°, and 25.5°±1°, preferably, has characteristic peaks at 2θ angles of 7.5°±1°, 9.5°±1°, 22.0°±1°, and 25.5°±1°; preferably, has characteristic peaks at 2θ angles of 7.5°±0.5°, 9.5°±0.5°, 22.0°±0.5°, and 25.5°±0.5°.
[0017] In a second aspect, the present invention provides a method for preparing a monolithic binder-free multi-stage pore MWW molecular sieve, the preparation method comprising the following steps:
[0018] (1) forming and drying a mixture comprising a first silicon source, a first aluminum source, and a second silicon source to obtain a precursor material containing amorphous silicon dioxide and an aluminum source;
[0019] (2) mixing the precursor material obtained in step (1) with a second aluminum source, a template, an alkali source and water, and then crystallizing to obtain an intermediate crystalline material;
[0020] (3) calcining the intermediate crystalline material obtained in step (2).
[0021] In some embodiments, the molar ratio of the first silicon source to the second silicon source, calculated as SiO2, is 1:(0.08-0.5), preferably 1:(0.1-0.4), for example 1:0.1, 1:0.15, 1:0.20, 1:0.25, 1:0.30, 1:0.35, 1:0.38.
[0022] In some embodiments, the molar ratio of the second aluminum source to the first aluminum source, calculated as Al2O3, is 1:(0.3-1.5), for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.3, 1:0.4, 1:1.5.
[0023] In some embodiments, the molar ratio of the second aluminum source to the first aluminum source is 1:(0.3-1.0) calculated as Al2O3.
[0024] In some embodiments, the molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.01-0.08). In some embodiments, the molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.02-0.08), for example, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05, 1:0.055, 1:0.06, 1:0.065, 1:0.07, 1:0.075, 1:0.08.
[0025] In some embodiments, the molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.02-0.06).
[0026] In some embodiments, the molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.001-0.3), for example 1:0.002, 1:0.005, 1:0.006, 1:0.008, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.08, 1:0.1, 1:0.15, 1:0.20, 1:0.25, 1:0.3, 1:0.35, 1:0.4.
[0027] In some embodiments, the molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.05-0.2).
[0028] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.005-0.2); preferably 1:(0.01-0.1), for example 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05, 1:0.065, 1:0.07, 1:0.08, 1:0.09, 1:0.1.
[0029] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the template is 1:(0.2-0.6), preferably 1:(0.2-0.5), for example 1:0.2, 1:0.3, 1:0.4, 1:0.5.
[0030] In some embodiments, the molar ratio of the total silicon source calculated as SiO2 to the alkali source is 1:(0.04-0.2), for example 1:0.05, 1:0.08, 1:0.1, 1:0.15, 1:0.20.
[0031] In some embodiments, the molar ratio of the total silicon source, calculated as SiO2, to water is 1:(10-30), for example 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:23 or 1:25.
[0032] In some embodiments, the drying temperature is 80-200°C, such as 90°C, 100°C, 120°C, 140°C, 160°C or 180°C, preferably 100-150°C.
[0033] In some embodiments, the drying time is 2 to 24 hours, preferably 3 to 10 hours.
[0034] In some embodiments, the calcination temperature is 450-1000° C., preferably 500-750° C. In some embodiments, the calcination temperature is 500° C., 550° C., 600° C., 650° C., 700° C., 720° C., 750° C. or 800° C.
[0035] In some embodiments, the calcination time is 1 to 12 hours, preferably 2 to 10 hours.
[0036] In some embodiments, the crystallization temperature is 130-200°C, preferably 140-190°C, for example 140°C, 150°C, 160°C, 170°C, 180°C or 190°C.
[0037] In some embodiments, the crystallization time is 12 to 100 hours, preferably 24 to 100 hours. In some embodiments, the crystallization time is 24 hours, 28 hours, 32 hours, 26 hours, 40 hours, 44 hours, 48 hours, 52 hours, 58 hours, 62 hours, 66 hours, 70 hours, 74 hours or 80 hours.
[0038] In some embodiments, the first silicon source includes one or more of solid silicon dioxide, silica gel, white carbon black, or silicon dioxide aerosol.
[0039] In some embodiments, the first aluminum source includes one or more of aluminum hydroxide, sodium aluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, aluminum sulfate, kaolin, or montmorillonite.
[0040] In some embodiments, the second aluminum source includes one or more of aluminum hydroxide, sodium metaaluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, or aluminum sulfate.
[0041] In some embodiments, the second silicon source is silica sol.
[0042] In some embodiments, the second silicon source is 10-50 wt % silica sol, preferably 35-45 wt % silica sol.
[0043] In some embodiments, the template agent includes an organic amine template agent; preferably, the organic amine template agent includes one or more of hexamethyleneimine, piperidine, homopiperazine, ethylenediamine, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide.
[0044] In some embodiments, the organic amine templating agent includes hexamethyleneimine.
[0045] In some embodiments, the alkali source comprises an alkali metal hydroxide; preferably, the alkali source is NaOH or KOH.
[0046] The molding may be mixed by adding a certain extrusion aid. The extrusion aid may be a conventional extrusion aid in the art. The extrusion aid may be one or more of sesbania powder, methyl cellulose, ethyl cellulose, graphite, starch, polyvinyl alcohol and polyacrylamide. In some embodiments of the present invention, the extrusion aid is sesbania powder.
[0047] In a third aspect, the present invention provides the use of the integral binderless multi-level pore MWW molecular sieve described in the first aspect of the present invention or the integral binderless multi-level pore MWW molecular sieve prepared by the preparation method described in the second aspect of the present invention as a catalyst in the production of isopropylbenzene.
[0048] In some embodiments, the feedstock for producing cumene contains polyisopropylbenzenes.
[0049] In some embodiments, the feedstock for producing cumene contains diisopropylbenzene.
[0050] In some embodiments, the feedstock for producing cumene contains benzene, diisopropylbenzene and propylene.
[0051] In a fourth aspect, the present invention provides a method for producing isopropylbenzene, wherein benzene, diisopropylbenzene and propylene are used as raw materials, and the raw materials are contacted with a catalyst to react to synthesize isopropylbenzene, and the catalyst is the integral binderless multi-level pore MWW molecular sieve described in the present invention or the integral binderless multi-level pore MWW molecular sieve prepared by the preparation method described in the present invention.
[0052] In some embodiments, the molar ratio of benzene to propylene is (1-6):1, and the molar ratio of benzene to diisopropylbenzene is (5-20):1.
[0053] In some embodiments, the molar ratio of benzene to propylene is (1-4):1, and the molar ratio of benzene to diisopropylbenzene is (5-15):1.
[0054] In some embodiments, the reaction temperature of the reaction is 120-250° C., and the reaction pressure is 1-5 MPa. In some embodiments, the reaction temperature of the reaction is 135-200° C., and the reaction pressure is 1-3.5 MPa.
[0055] In some embodiments, the weight space velocity of propylene is 1 to 10 h -1 , for example 1h -1 , 3h -1 , 5h -1 , 7h -1 or 9h -1 .
[0056] In some embodiments, the weight space velocity of propylene is 1 to 8 h -1 .
[0057] The integral binder-free multi-level pore MWW molecular sieve provided by the present invention has micropores and mesopores, and the mesopores account for more than 65% of the total pore volume. When isopropylbenzene is produced from benzene, diisopropylbenzene and propylene as raw materials, the specific pore structure is suitable for the alkylation reaction of benzene, diisopropylbenzene and propylene, and has the characteristics of high activity, good selectivity, few by-products and simple process flow in this type of reaction.
[0058] The preparation method of the method of the present invention utilizes the characteristic that the guiding ability of the small molecule organic amine template agent is relatively weak during the crystallization process of the molecular sieve, so that the precursor containing the amorphous silicon dioxide material and the aluminum source material is converted into a monolithic binder-free MWW molecular sieve in situ. Due to the interface shrinkage effect during the crystallization process, many regularly arranged mesopores are generated. The monolithic binder-free MWW molecular sieve of the present invention has both a regular mesoporous structure and two sets of microporous structures and lamellar morphology that are unique to the MWW molecular sieve. When the molecular sieve is applied to the reaction of catalyzing the alkylation of benzene, diisopropylbenzene and propylene, it has the advantages of good catalytic activity, faster material diffusion speed and more stable catalyst performance.
[0059] By using the multi-stage pore MWW molecular sieve of the present invention, not only two reactors are not needed to separate polyisopropylbenzenes, but the conversion rate of polyisopropylbenzenes is also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The accompanying drawings are used to provide further understanding of the present application and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present application, but do not constitute a limitation to the present application.
[0061] Figure 1 This is the XRD spectrum of the monolithic binder-free MWW molecular sieve prepared in Example 1 of the present invention.
[0062] Figure 2This is the XRD spectrum of the MWW molecular sieve synthesized by the traditional method and formed by the binder in Comparative Example 1 of the present invention.
[0063] Figure 3 This is the N2 adsorption-desorption curve of the integral binder-free MWW molecular sieve prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0065] The endpoints and any values of the ranges disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Reaction space velocity refers to the amount of gas treated by a unit volume of catalyst per unit time under specified conditions, and the unit is m 3 / (m 3 catalyst·h), which can be simplified to h -1 .
[0066] The molecular sieve crystal phase analysis was carried out using a Rigaku-Ultima X-ray diffractometer from Japan. The XRD test conditions were: CuKα radiation, wavelength λ=0.15432nm; X-ray diffraction pattern scanning range 2θ=5°~50°, scanning speed 10° / min, working voltage 40kV, current 40mA.
[0067] The average pore size and total pore volume of the molecular sieve were determined by N2 physical adsorption. The test method is as follows: the specific surface area (BET) and pore volume of the sample were analyzed by using the Autosorb-I automatic adsorption specific surface and porosity analyzer produced by Quantachrome Company of the United States, wherein the cold trap was liquid nitrogen and the adsorption medium was high-purity nitrogen; the adsorption isotherm equation of the HK model was used to analyze the low-pressure section of the adsorption isotherm to obtain the pore size distribution curve of the molecular sieve; the specific surface area and pore volume of the molecular sieve were calculated by the BET method and the t-plot method, respectively.
[0068] The product was analyzed by gas chromatography. A certain amount of the reaction mixture was injected from the gas chromatograph injection port, detected by FID after passing through the chromatographic column, and quantitatively analyzed by external standard method. The gas chromatograph used was a 7890 gas chromatograph produced by Agilent, and the analytical chromatographic column used was an INNOWAX column.
[0069] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0070] The term "wt%" means percent by mass.
[0071] In the following, all numbers disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% will be explicitly disclosed, where "+ / -" means plus or minus.
[0072] The calculation formulas for conversion rate and selectivity in the application example are as follows:
[0073] Selectivity of isopropylbenzene or triisopropylbenzene IPB / DIPB =Mass percentage of isopropylbenzene or triisopropylbenzene / (mass percentage of each chromatographic product and by-product)×100%.
[0074] Conversion rate of benzene or propylene X BEN / PE =(initial concentration of benzene or propylene-end concentration of benzene or propylene) / (initial concentration of benzene or propylene)×100%.
[0075] The conversion rate of diisopropylbenzene is X DIPB =(the number of moles of diisopropylbenzene at the outlet of the alkylation reactor per unit time - the number of moles of diisopropylbenzene at the inlet of the alkylation reactor per unit time) / (the number of moles of diisopropylbenzene at the inlet of the alkylation reactor per unit time)×100%.
[0076] The method for determining the amount of molecular sieve acid in the application example is as follows:
[0077] Weigh 0.5 g of molecular sieve powder, add 100 ml of water, stir for 10 minutes, add 0.2 g of piperidine, stir for 30 minutes, add 2 drops of phenolphthalein, and titrate with a 0.2 mol / L potassium hydrogen phthalate aqueous solution until the phenolphthalein changes color. Calculate the volume of potassium hydrogen phthalate aqueous solution used for titration and calculate the acid amount of the molecular sieve in millimoles / gram. The calculation formula is as follows:
[0078] Molecular sieve acid amount = (weight of piperidine / 85.15-concentration of potassium hydrogen phthalate×volume of potassium hydrogen phthalate / 1000) / weight of molecular sieve×1000.
[0079] Example
[0080] Examples 1-10 were prepared using the following method:
[0081] 1) Mix the first silicon source and the first aluminum source, add an appropriate amount of an extrusion aid (the extrusion aid may be one or more of sesbania powder, methyl cellulose, ethyl cellulose, graphite, starch, polyvinyl alcohol and polyacrylamide. In some embodiments of the present invention, the extrusion aid used is sesbania powder) with the second silicon source, and shape them into strips with a diameter of 1 mm and a length of 0.5 cm. Dry the strips after the above shaping at a certain temperature for a certain time to obtain a precursor silicon material.
[0082] 2) A certain mass of the second aluminum source, template, alkali source and H2O are dissolved and mixed; the precursor silicon material is added to the mixture. Crystallization is carried out at a certain temperature for a certain time to obtain an intermediate crystalline material. The intermediate crystalline material is taken out from the liquid, washed with deionized water, dried, and calcined in a muffle furnace at a certain temperature for a certain time to obtain a monolithic binder-free MWW molecular sieve.
[0083] The reaction conditions of each embodiment are shown in Table 1, and the reaction materials and amounts are shown in Table 2:
[0084] Table 1: Reaction conditions
[0085]
[0086]
[0087] Table 2: Reaction materials
[0088]
[0089]
[0090] Table 2 continued
[0091]
[0092] Parameter test results of Examples 1-10:
[0093] Example 1: XRD characterization results of molecular sieves are as follows Figure 1 The N2 physical adsorption characterization results are shown in Figure 3 As shown. Figure 1 It can be seen that the molecular sieve is a typical MWW molecular sieve. Figure 3 The hysteresis loop was observed, which confirmed the existence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 26% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 34% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 32% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 8% of the total pore volume. The average pore diameter was 3.7 nm, and the total pore volume was 0.51 cm 3 / g, micropore volume is 0.31cm 3 / g, specific surface area is 485m 2 / g. The acid content of the molecular sieve is 1.20 mmol / g.
[0094] Example 2: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 29% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 31% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 10% of the total pore volume. The average pore diameter was 4.1 nm, and the total pore volume was 0.53 cm 3 / g, micropore volume is 0.37cm 3 / g, specific surface area is 482m 2 / g. The acid content of the molecular sieve is 1.34 mmol / g.
[0095] Example 3: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 21% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 35% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 37% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 7% of the total pore volume. The average pore diameter was 4.0 nm, and the total pore volume was 0.60 cm 3 / g, micropore volume is 0.41cm 3 / g, specific surface area is 510m 2 / g. The acid content of the molecular sieve is 1.12 mmol / g.
[0096] Example 4: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size of less than 2.0 nm accounted for 29% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 33% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 8% of the total pore volume. The average pore diameter was 3.5 nm, and the total pore volume was 0.38 cm 3 / g, micropore volume is 0.28cm 3 / g, specific surface area is 452m 2 / g. The acid content of the molecular sieve is 1.45 mmol / g.
[0097] Example 5: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 35% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 27% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 9% of the total pore volume. The average pore diameter was 3.7 nm, and the total pore volume was 0.40 cm 3 / g, micropore volume is 0.29cm 3 / g, specific surface area is 467m 2 / g. The acid content of the molecular sieve is 1.37 mmol / g.
[0098] Example 6: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size of less than 2.0 nm accounted for 31% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 32% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 25% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 12% of the total pore volume. The average pore diameter was 3.6 nm, and the total pore volume was 0.55 cm 3 / g, micropore volume is 0.32cm 3 / g, specific surface area is 503m 2 / g. The acid content of the molecular sieve is 1.31 mmol / g.
[0099] Example 7: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size of less than 2.0 nm accounted for 24% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 37% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 29% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 10% of the total pore volume. The average pore diameter was 3.8 nm, and the total pore volume was 0.54 cm 3 / g, micropore volume is 0.42cm 3 / g, specific surface area is 520m 2 / g. The acid content of the molecular sieve is 1.42 mmol / g.
[0100] Example 8: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 28% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 31% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 32% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 9% of the total pore volume. The average pore diameter was 3.9 nm, and the total pore volume was 0.62 cm 3 / g, micropore volume is 0.35cm 3 / g, specific surface area is 550m 2 / g. The acid content of the molecular sieve is 1.28 mmol / g.
[0101] Example 9: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 34% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 26% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 30% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 10% of the total pore volume. The average pore diameter was 3.8 nm, and the total pore volume was 0.47 cm 3 / g, micropore volume is 0.33cm 3 / g, specific surface area is 497m 2 / g. The acid content of the molecular sieve is 1.50 mmol / g.
[0102] Example 10: Characterization results of molecular sieve N2 physical adsorption. Hysteresis loops were observed, which confirmed the presence of mesopores. The pore volume with a pore size less than 2.0 nm accounted for 23% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 30% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 36% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 11% of the total pore volume. The average pore diameter was 4.2 nm, and the total pore volume was 0.59 cm 3 / g, micropore volume is 0.39cm 3 / g, specific surface area is 526m 2 / g. The acid content of the molecular sieve is 1.03 mmol / g.
[0103] Application Method
[0104] 1 g of the prepared monolithic binder-free MWW molecular sieve was loaded into a fixed bed reactor, and a mixture of benzene, diisopropylbenzene and propylene was introduced at a reaction temperature of 140°C, a reaction pressure of 2.5 MPa, and a space velocity of propylene of 1.5 h -1 , the molar ratio of benzene to propylene is 2.0:1, and the molar ratio of benzene to diisopropylbenzene is 10.0:1. The reaction results of Examples 1-10 are shown in Table 3:
[0105] Table 3: Example reaction results
[0106]
[0107]
[0108] Examples 1A-1F
[0109] Except that the molar ratio of the first silicon source calculated as SiO2 and the first and second aluminum sources calculated as Al2O3 is different from that in Example 1 (see Table 4 below for details), the other reaction conditions and reaction materials are the same as those in Example 1.
[0110] Parameter test results:
[0111] Example 1A: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 36% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 32% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 23% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 9% of the total pore volume. The average pore diameter was 3.1 nm, and the total pore volume was 0.36 cm 3 / g, micropore volume is 0.24cm 3 / g, specific surface area is 402m 2 / g. The acid content of the molecular sieve is 0.98 mmol / g.
[0112] Example 1B: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 21% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 35% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 41% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 4% of the total pore volume. The average pore diameter was 3.3 nm, and the total pore volume was 0.30 cm 3 / g, micropore volume is 0.26cm 3 / g, specific surface area is 421m 2 / g. The acid content of the molecular sieve is 0.97 mmol / g.
[0113] Example 1C: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 26% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 27% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 42% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 5% of the total pore volume. The average pore diameter was 3.1 nm, and the total pore volume was 0.33 cm 3 / g, micropore volume is 0.24cm 3 / g, specific surface area is 433m 2 / g. The acid content of the molecular sieve is 1.02 mmol / g.
[0114] Example 1D: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 23% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 32% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 30% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 15% of the total pore volume. The average pore diameter was 2.7 nm, and the total pore volume was 0.31 cm 3 / g, micropore volume is 0.22cm 3 / g, specific surface area is 380m 2 / g. The acid content of the molecular sieve is 0.99 mmol / g.
[0115] Example 1E: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 26% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 34% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 24% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 16% of the total pore volume. The average pore diameter was 4.3 nm, and the total pore volume was 0.65 cm 3 / g, micropore volume is 0.21cm 3 / g, specific surface area is 440m 2 / g. The acid content of the molecular sieve is 0.89 mmol / g.
[0116] Example 1F: No hysteresis loop was observed. The pore volume with a pore size of less than 2.0 nm accounted for 19% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounted for 36% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounted for 36% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounted for 9% of the total pore volume. The average pore diameter was 3.4 nm, and the total pore volume was 0.36 cm 3 / g, micropore volume is 0.24cm 3 / g, specific surface area is 412m 2 / g. The acid content of the molecular sieve is 0.95 mmol / g.
[0117] Reaction results: The same application method as in Example 1 was used. The reaction results are shown in Table 4:
[0118] Table 4: Reaction results
[0119]
[0120] Comparative Example
[0121] Comparative Example 1
[0122] 28.94g of 40% silica sol, 1.65g of aluminum sulfate, 3.81g of hexamethyleneimine, 0.77g of NaOH and 1.98g of H2O5 were dissolved and mixed. The molar ratio of SiO2, Al2O3, hexamethyleneimine, NaOH and water in the mixture was 1:0.025:0.2:0.10:15. Crystallize at 180°C for 48 hours to obtain the original molecular sieve powder. The original powder was filtered, washed with deionized water and dried. The obtained powder was formed into strips with a diameter of 1 mm and a length of 0.5 cm by adding a proper amount of extrusion aid with pseudo-boehmite and 5% dilute nitric acid. The mass ratio of the original powder to alumina was 6.5:3.5. The above-formed strips were dried at 120°C for 3h. The dried strips were calcined at 550°C in a muffle furnace for 5 hours to obtain the MWW molecular sieve synthesized by the traditional method and formed with a binder.
[0123] Parameter test results:
[0124] The XRD characterization results of the above molecular sieves are as follows Figure 2 As shown. Figure 2 It can be seen that the molecular sieve is a typical MWW molecular sieve. Similar to the test method of Example 1 above, no hysteresis loop is observed, and the average pore diameter of the molecular sieve is 2.0 nanometers, and the total pore volume is 0.15 cm 3 g -1 , the micropore volume is 0.10cm3 g -1 The pore volume with a pore size less than 2.0 nm accounts for 51% of the total pore volume, the pore volume with a pore size of 2.0-5.0 nm accounts for 35% of the total pore volume, the pore volume with a pore size of 5.0-20.0 nm accounts for 10% of the total pore volume, and the pore volume with a pore size greater than 20.0 nm to 50.0 nm accounts for less than 5% of the total pore volume. The specific surface area of the MWW molecular sieve is 279 cm 2 / g. The acid content of the molecular sieve is 1.15 mmol / g.
[0125] Reaction results:
[0126] The same application method as in Example 1 was used. The conversion rate of propylene was 100%, the selectivity of isopropylbenzene was 82.5%, the conversion rate of diisopropylbenzene was 3.2%, and the selectivity of triisopropylbenzene was 1.86%.
[0127] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A monolithic binder-free multi-stage pore MWW molecular sieve, wherein: The molecular sieve has micropores and mesopores, wherein the micropores are pores with a pore diameter less than 2 nm, and the mesopores are pores with a pore diameter of 2 to 50 nm, and the mesopores account for more than 65% of the total pore volume; Preferably, the mesopores include first mesopores, second mesopores and third mesopores, the pore size d1 of the first mesopores satisfies: 2.0nm<d1≤5.0nm, the pore size d2 of the second mesopores satisfies: 5.0nm<d2≤20nm, and the pore size d3 of the third mesopores satisfies: 20nm<d3<50nm.
2. The MWW molecular sieve according to claim 1, characterized in that The molecular sieve has one or more of the following characteristics (a) to (h): (a) The acid amount of the molecular sieve is 1 to 2 mmol / g, preferably 1 to 1.5 mmol / g; (b) The specific surface area of the molecular sieve is 450 to 600 m 2 / g, preferably 450 to 550 m 2 / g; (c) the average pore size of the molecular sieve is 3 to 5 nm, preferably 3.2 to 4.5 nm; (d) The total pore volume of the molecular sieve is 0.25 to 0.75 cm 3 / g, preferably 0.30 to 0.70 cm 3 / g; (e) The micropore volume of the molecular sieve is 0.25 to 0.45 cm 3 / g, preferably 0.28 to 0.42 cm 3 / g; (f) the pore volume of the first mesopores accounts for 25% to 40% of the total pore volume, the pore volume of the second mesopores accounts for 25% to 40% of the total pore volume, and the pore volume of the third mesopores accounts for less than 15% of the total pore volume, preferably 7-12%; (g) The molecular sieve has a closed hysteresis loop at P / P0=0.4-0.99 on the nitrogen adsorption-desorption curve, and the absorption mass difference between the adsorption curve and the desorption curve is 0-4cm 2 / g; preferably, the starting position of the closed hysteresis loop is at P / P0=0.45-0.99, and the absorption mass difference between the adsorption curve and the desorption curve is 0-3.5cm 2 / g; (h) The molecular sieve X-ray diffraction (XRD) spectrum has characteristic peaks at 2θ angles of 7.5°±1°, 9.5°±1°, and 25.5°±1°, preferably, has characteristic peaks at 2θ angles of 7.5°±1°, 9.5°±1°, 22.0°±1°, and 25.5°±1°, and further preferably, has characteristic peaks at 2θ angles of 7.5°±0.5°, 9.5°±0.5°, 22.0°±0.5°, and 25.5°±0.5°.
3. A method for preparing a monolithic binder-free multi-stage pore MWW molecular sieve, comprising the following steps: (1) forming and drying a mixture comprising a first silicon source, a first aluminum source, and a second silicon source to obtain a precursor material containing amorphous silicon dioxide and an aluminum source; (2) mixing the precursor material obtained in step (1) with a second aluminum source, a template, an alkali source and water, and then crystallizing to obtain an intermediate crystalline material; (3) calcining the intermediate crystalline material obtained in step (2).
4. The preparation method according to claim 3, characterized in that: Calculated in terms of SiO2, the molar ratio of the first silicon source to the second silicon source is 1:(0.1-0.4); and / or, Calculated in terms of Al2O3, the molar ratio of the second aluminum source to the first aluminum source is 1:(0.3-1.5), preferably 1:(0.3-1.0); and / or, The molar ratio of the first silicon source calculated as SiO2 to the first aluminum source calculated as Al2O3 is 1:(0.02-0.08), preferably 1:(0.02-0.06); and / or, The molar ratio of the second silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.001-0.3), preferably 1:(0.05-0.2); and / or, The molar ratio of the total silicon source calculated as SiO2 to the second aluminum source calculated as Al2O3 is 1:(0.005-0.2), preferably 1:(0.01-0.1); and / or, The molar ratio of the total silicon source, calculated as SiO2, to the template is 1:(0.2-0.6); and / or, The molar ratio of the total silicon source, calculated as SiO2, to the alkali source is 1:(0.04-0.2); and / or, The molar ratio of the total silicon source calculated as SiO2 to water is 1:(10-30).
5. The preparation method according to claim 3 or 4, characterized in that: The drying temperature is 80 to 200° C., preferably 100 to 150° C.; the drying time is 2 to 24 hours, preferably 3 to 10 hours; and / or The calcination temperature is 450-1000° C., preferably 500-750° C.; the calcination time is 1-12 hours, preferably 2-10 hours; and / or The crystallization temperature is 130-200° C., preferably 140-190° C.; the crystallization time is 12-100 hours, preferably 24-100 hours.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The first silicon source comprises one or more of solid silicon dioxide, silica gel, white carbon black or silicon dioxide aerosol; and / or The first aluminum source comprises one or more of aluminum hydroxide, sodium aluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride, aluminum sulfate, kaolin or montmorillonite; and / or The second aluminum source includes one or more of aluminum hydroxide, sodium aluminate, aluminum isopropoxide, aluminum nitrate, anhydrous aluminum chloride or aluminum sulfate; and / or The second silicon source is 10-50wt% silica sol; preferably 35-45wt% silica sol; and / or The template agent includes an organic amine template agent; preferably, the organic amine template agent includes one or more of hexamethyleneimine, piperidine, homopiperazine, ethylenediamine, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide; preferably, the organic amine template agent includes hexamethyleneimine; and / or The alkali source includes alkali metal hydroxide; preferably, the alkali source is NaOH or KOH.
7. Use of the monolithic binderless multi-level pore MWW molecular sieve according to claim 1 or 2 or the monolithic binderless multi-level pore MWW molecular sieve prepared by the preparation method of any one of claims 3 to 6 as a catalyst in the production of cumene; Preferably, the raw material for producing cumene contains polyisopropylbenzene; preferably contains diisopropylbenzene; more preferably contains benzene, diisopropylbenzene and propylene.
8. A method for producing cumene, wherein: Benzene, diisopropylbenzene and propylene are used as raw materials, and the raw materials are contacted with a catalyst to react to synthesize cumene. The catalyst is the integral binder-free multi-level pore MWW molecular sieve described in claim 1 or 2 or the multi-level pore MWW molecular sieve prepared by the preparation method described in claims 3-6.
9. The method according to claim 8, characterized in that The molar ratio of benzene to propylene is (1-6):1, and the molar ratio of benzene to diisopropylbenzene is (5-20):1; preferably, the molar ratio of benzene to propylene is (1-4):1, and the molar ratio of benzene to diisopropylbenzene is (5-15):
1.
10. The method according to claim 8 or 9, characterized in that: The reaction temperature of the reaction is 120-250°C, the reaction pressure is 1-5 MPa, and the weight space velocity of propylene is 1-10 h -1 Preferably, the reaction temperature is 135-200°C, the reaction pressure is 1-3.5 MPa, and the weight space velocity of propylene is 1-8 h -1 .
Citation Information
Patent Citations
Method for producing isopropylbenzene
CN102464563A
Method for producing isopropylbenzene
CN102464564A
Method for producing isopropylbenzene by using benzene and propylene
CN102464565A
Hierarchical porous SAPO-18 molecular sieve, preparation method thereof and application thereof
CN105417552A
Preparation method of binderless MWW structural molecular sieve
CN107512727A